METODE YASINIYAH SEBAGAI METODE PEMBELAJARAN MEMBACA AL-QUR’AN - Munir Munir (Ta'dib: Jurnal Pendidikan Islam, 2010)
This article is research report on the implementation of Yasiniyah method in learning of reading al-Qur’an. The research use theories of phenomenology–symbolic-interactionism for understanding reality in application of this method. For anlyzing the meaning  of reality, it need the approach of social-psichology with contrast analysis, verification and comparation with another different reality. Yasiniah method, philosophically, is based on pesantren’s classic tradition. The characteristic of Yasiniah method can be seen in its system of implementation, i.e. : 1) recruitment system of new student; 2) system of class management; 3) learning material; 4) strategy implemented; 5) system of evaluation use test or directly oral examination  by facing mustahiq individually, and who can pass the exam will be given the certificate at alumni’s release ceremony in  every end of academic year.